Assessment of dose homogeneity in conformal interstitial breast brachytherapy with special respect to ICRU recommendations - Major, Tibor; Fröhlich, Georgina; Polgar, Csaba (Journal of Contemporary Brachytherapy, 2011)
Purpose : To present the results of dose homogeneity analysis for breast cancer patients treated with image-based conformal interstitial brachytherapy, and to investigate the usefulness of the ICRU recommendations. Material and methods : Treatment plans of forty-nine patients who underwent partial breast irradiation with interstitial brachytherapy were analyzed. Quantitative parameters were used to characterize dose homogeneity. Dose non-uniformity ratio (DNR), dose homogeneity index (DHI), uniformity index (UI) and quality index (QI) were calculated. Furthermore, parameters recommended by the ICRU 58 such as minimum target dose (MTD), mean central dose (MCD), high dose volume, low dose volume and the spread between local minimum doses were determined. Correlations between the calculated homogeneity parameters and usefulness of the ICRU parameters in image-based brachytherapy were investigated. Results : Catheters with mean number of 15 (range: 6-25) were implanted in median 4 (range: 3-6) planes. The volume of the PTV ranged from 15.5 cm 3 to 176 cm 3 . The mean DNR was 0.32, the DHI 0.66, the UI 1.49 and the QI 1.94. Related to the prescribed dose, the MTD was 69% and the MCD 135%. The mean high dose volume was 8.1 cm 3 (10%), while the low dose volume was 63.8 cm 3 (96%). The spread between minimum doses in central plane ranged from –14% to +20%. Good correlation was found between the DNR and the DHI (R2 = 0.7874), and the DNR correlated well with the UI (R2 = 0.7615) also. No correlation was found between the ICRU parameters and any other volumetric parameters. Conclusions : To characterize the dose uniformity in high-dose rate breast implants, DVH-related homogeneity parameters representing the full 3D dose distributions were mandatory to be used. In many respects the current recommendations of the ICRU Report 58 are already outdated, and it is well-timed to set up new recommendations, which are more feasible for image-guided conformal interstitial brachytherapy.